1999
DOI: 10.1093/jjco/29.8.395
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma Metastatic to the Kidneys Without Lung Involvement

Abstract: Symptomatic renal metastasis is very rare in osteosarcoma. A few reported cases had pulmonary metastases before renal involvement. We present a case of metastatic renal osteosarcoma without pulmonary involvement. The patient presented with hematuria 8 years after initial treatment of osteosarcoma of the left distal femur. Computed tomography revealed a bilateral calcified renal mass. The patient died of disease 4 months after detection of the metastases. At autopsy, metastatic osteosarcoma was discovered in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Its clinical symptoms, sometimes insidious, can delay diagnosis. The clinical features, the chronology of the lesions, a good tumor sampling and immunohistochemistry (cytokeratin AE1/AE3) can help in the differentiation between a carcinoma and a sarcoma of the kidney [7,[23][24][25]. Our case of an elderly patient presenting with total hematuria, which eventually led to the diagnosis of a high-grade primary renal osteoblastic osteosarcoma, is the 28th case of primary renal osteosarcoma reported in the literature and underlines the need of an early diagnosis of this highly malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical symptoms, sometimes insidious, can delay diagnosis. The clinical features, the chronology of the lesions, a good tumor sampling and immunohistochemistry (cytokeratin AE1/AE3) can help in the differentiation between a carcinoma and a sarcoma of the kidney [7,[23][24][25]. Our case of an elderly patient presenting with total hematuria, which eventually led to the diagnosis of a high-grade primary renal osteoblastic osteosarcoma, is the 28th case of primary renal osteosarcoma reported in the literature and underlines the need of an early diagnosis of this highly malignant tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Des cas d'ostéosarcomes métastatiques au niveau du rein ont été signalés et il est important de pratiquer un bilan osseux complet pour élimi-ner cette possibilité diagnostique 8,9 . Le pronostic est très mauvais; il rejoint celui des autres sarcomes du rein.…”
Section: Discussionunclassified
“…However, a more recent literature review found a mean interval of 62 months from time of treatment of primary tumor to diagnosis of renal metastases [12]. …”
Section: Discussionmentioning
confidence: 99%